THE STAGES OF DEVELOPING COMMUNICATIVE COMPETENCE IN THE PROCESS OF TEACHING FOREIGN LANGUAGES. - Rakhmonqulova Dilshoda Murodkuziyevna (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract:  This  article  explores  the  stages  of  developing  communicative competence  in  foreign  language  teaching.  It  emphasizes  the  importance  of communicative  competence  as  a  core  objective  in  language  education,  outlining  a systematic approach that teachers can adopt to enhance students’ language skills. The stages discussed include awareness, practice, application, and assessment, each playing a crucial role in fostering effective communication abilities. The article aims to provide educators with practical strategies to implement these stages in their teaching practices.